Noninvasive options for 'wearing-off' in Parkinson's disease: a clinical consensus from a panel of UK Parkinson's disease specialists. (5th July 2018) - Fackrell, Robin; Carroll, Camille B; Grosset, Donald G; Mohamed, Biju; Reddy, Prashanth; Parry, Miriam; Chaudhuri, Kallol Ray; Foltynie, Tom
In the past 4 years, two adjunctive treatment options to levodopa have been licensed for use in the UK in patients with Parkinson's disease (PD) and motor fluctuations: opicapone, a third-generation catechol-O-methyl transferase inhibitor, and safinamide, a monoamine oxidase B inhibitor. This clinical consensus outlines the practical considerations relating to motor fluctuations and managing wearing-off in patients with PD, and provides a clinical insight to adjunctive treatment options, including opicapone and safinamide. Practice-based opinion was provided from a multidisciplinary steering Group of eight UK-based movement disorder and PD specialists, including neurologists, geriatricians and a nurse specialist, from England, Scotland and Wales.